Heat Treatment of Sprayed Coatings - Yu. V. Sokolov; M. A. Sadokha; D. A. Popok (Наука и техника)
The paper reveals an effect of heat-cyclic treatment (HCT) on the structure and properties of NiCuBSi system coatings. This system is recommended to be used as powder for manufacturing mould dies with the help of plasma spraying. Calculation of optimum HCT regimes ensuring the best combination of physical and mechanical properties of coatings is given in the paper.